2019
DOI: 10.1016/j.omto.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

ZNF280A Promotes Proliferation and Tumorigenicity via Inactivating the Hippo-Signaling Pathway in Colorectal Cancer

Abstract: Aberrant expression of zinc-finger proteins has been extensively reported to contribute to malignant progression in a variety of cancers. However, clinical significance and biological roles of ZNF280A in the field of cancer are poorly known. In this study, the expression of ZNF280A was detected in clinical colorectal cancer (CRC) tissues. Functional experiments in vitro and animal experiment in vivo were performed to measure the effect of ZNF280A on the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…vating β-catenin. 36,37 In our previous study, 26,27 we explored the role of the Hippo signaling pathway in CRC. By performing bioinformatic analysis and cell experiments, we found that DLG2, the target gene of miR-942-5p, was also with a player in the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…vating β-catenin. 36,37 In our previous study, 26,27 we explored the role of the Hippo signaling pathway in CRC. By performing bioinformatic analysis and cell experiments, we found that DLG2, the target gene of miR-942-5p, was also with a player in the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we found that aberrant Hippo signaling participated in CRC progression. 26,27 Hence, we pondered whether the positive regulation of DLG2 was related to CRC inhibition via the Hippo signaling pathway. Plenty of evidence suggests that hippo signaling activation is a hall marker of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ZNF280A has been reported to be absent in hematopoietic malignancies, including peripheral cell lymphoma and chronic lymphocytic leukemia, suggesting that ZNF280A may play a role in tumor suppression in hematopoietic malignancies [27]. Conversely, Wang et al, suggested that ZNF280A promotes effort and tumorigenicity via inactivating the Hippo-signaling pathway in colorectal cancer [28]. The above findings on ZNFs in other cancers prompt us to explore the role of ZNF280A in OC.…”
Section: Discussionmentioning
confidence: 99%